Impact of ultraviolet C radiation and ozone application on the physiological quality of organic maize seeds - Maia, Mayana Pereira; Machado Silva, Carine Gregório; Martins, Guilherme Rodrigues; Silva, Danielle de Oliveira; Pereira, Ana Luiza Xavier; Mamedes, Artur de Souza; dos Passos, Alexandre Martins Abdão (International Journal of Advanced Engineering Research and Science, 2023)
Non-thermal energy sources have been utilized to control diseases and boost the physiological quality of maize seeds. The aim of this paper was to assess the impact of UV-c exposure and ozone application, associated or not, on organic maize seed germination and seedling vigor. Three cultivars (BRS Caimbé, BRS 1060 and BR 451), three exposure levels to ozone (15, 30 and 60 minutes) in the absence and presence of ultraviolet radiation (UV-c), were used in a completely randomized design with a factorial scheme of 3 x 3 x 2 + 3 (additional treatments) experiment. Evaluations of electrical conductivity, emergence in soil, and germination (at 4th and 7th day) on paper roll were done. Daily measurements of the emerged seedlings were taken up to the 14th day after emergence. The measurements included total emergence (EC), coefficient of variation in emergence time (CVt) in percentage, coefficient of emergence velocity (CVe) in percentage, emergence rate index (ERI) in days, and emergence synchronization index (Z). The tested genotypes caused differences in all studied variables. Increasing the percentage with a 30-minute exposure to ozone in the presence of UV-C radiation resulted in a validated enhance in the first germination reading. The association of O3 and UV-c techniques can be used to treat organic maize seeds without significantly affecting their physiological quality.